1998
DOI: 10.1098/rspb.1998.0264
|View full text |Cite
|
Sign up to set email alerts
|

No association between sexual size dimorphism and life histories in spiders

Abstract: In spiders, females are commonly larger than males. The majority of hypotheses that attempt to explain sexual size dimorphism in spiders concentrate on reduction in male size, although there is evidence to suggest that the independent evolution of marked sexual size dimorphism and reversion to a less extreme dimorphic state has occurred several times. Recent debate has centred on two con£icting hypotheses involving male dwar¢sm and increased female size through fecundity selection, and has focused on the golde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 32 publications
0
73
1
3
Order By: Relevance
“…Although sexual size dimorphism is common in spiders (15)(16)(17), it is extreme in the cobweb spider, Tidarren (Araneae, Theridiidae) (18)(19)(20). In this genus, sexual size dimorphism results from a decrease in male size (19,21,22) and an increase in female size (20).…”
mentioning
confidence: 99%
“…Although sexual size dimorphism is common in spiders (15)(16)(17), it is extreme in the cobweb spider, Tidarren (Araneae, Theridiidae) (18)(19)(20). In this genus, sexual size dimorphism results from a decrease in male size (19,21,22) and an increase in female size (20).…”
mentioning
confidence: 99%
“…Unique secondary sexual characters have clearly evolved only in males, but increasing numbers of studies document evolution only in females, in some cases via loss in females of character states that evolved earlier in both sexes (Bjö rklund 1991a,b;Wright 1993;Emerson 1994;Irwin 1994;Andersen 1997;Burns 1998;Wiens 1999Wiens , 2001Emlen 2000;Figuerola and Green 2000). Similarly, recent phylogenetic studies on size dimorphism have reported a variety of pathways to extant patterns (e.g., Coddington et al 1997;Fairbairn 1997;Prenter et al 1998;Hormiga et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual size dimorphism is common in several families; e.g., Araneidae (Foelix 1996;Roberts 1996), and the evolution of spider size dimorphism has been much discussed (Vollrath & Parker 1992;Coddington et al 1997;Vollrath 1998;Prenter et al 1997Prenter et al , 1999. For instance, in web-builders it has been argued that males spend more time searching for females that are often sedentary in their webs.…”
Section: Selective Predationmentioning
confidence: 99%